A new species of Liotyphlops (Serpentes: Anomalepididae) from the Atlantic Rain Forest of Northeastern Brazil - Freire, Eliza Maria Xavier; Caramaschi, Ulisses; Argôlo, Antônio Jorge Suzart (Zootaxa, 2007)
A new species of the genus Liotyphlops, known from three localities in the states of Alagoas and Bahia, in the Atlantic Rain Forest of Northeastern Brazil, is described. Liotyphlops trefauti sp. nov. is distinguished from all other species of the genus by the following combination of characters: four scales contacting the posterior edge of prefrontal; one scale contacting the posterior edge of nasal, between the second supralabial and the frontal; five scales in the first vertical row of lateral head scales; 22-22-22 scales around body; 520–543 dorsal scales; 499–532 ventral scales; absence of eye spot; and dorsal and ventral color bright yellowish-brown to reddish-brown.